2011
DOI: 10.1128/aac.00146-11
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent Hepatitis C Virus NS5A Inhibitors with Dimeric Structures

Abstract: The exceptional in vitro potency of the hepatitis C virus (HCV) NS5A inhibitor BMS-790052 has translated into an in vivo effect in proof-of-concept clinical trials. Although the 50% effective concentration (EC 50 ) of the initial lead, the thiazolidinone BMS-824, was ϳ10 nM in the replicon assay, it underwent transformation to other inhibitory species after incubation in cell culture medium. The biological profile of BMS-824, including the EC 50 , the drug concentration required to reduce cell growth by 50% (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 19 publications
1
58
0
Order By: Relevance
“…Symmetry and dimeric structures are apparently important contributors to the antiviral activities of NS5A inhibitors (5,7). Biochemical studies have also suggested that these inhibitors directly bind to NS5A (5, 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symmetry and dimeric structures are apparently important contributors to the antiviral activities of NS5A inhibitors (5,7). Biochemical studies have also suggested that these inhibitors directly bind to NS5A (5, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications describe how small compounds, which apparently target NS5A, inhibit replication with extreme potency, highlighting the validity of NS5A as a target for drug development (5)(6)(7). NS5A is a nonstructural protein that has no defined role in the virus life cycle but is absolutely required for RNA replication (8 -10) and particle assembly (11)(12)(13)(14).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…As a result of these findings, HPLC biogram fractionation experiments were performed, an exercise that traced potent HCV inhibitory activity to two minor components in the media identified as isomers of the dimeric species 48 (Figure 1). 17 The connectivity of the dimer was established by 1 H and 13 C NMR to be at the C-5 methine carbon, with the less mobile isomer on reversed phase LC analysis being the more potent compound, EC 50 = 0.6 nM, and which converted to the more mobile but less potent (EC 50 = 43 nM) isomer upon heating at 55°C. 17 In considering how compounds 46-48 might be generated, it was recognized that hydrogen abstraction at the C-5 methine carbon of 18 would form a classic captodative radical stabilized by the electron donating sulfur atom and the electron withdrawing carbonyl group.…”
Section: 15mentioning
confidence: 99%
“…17 The connectivity of the dimer was established by 1 H and 13 C NMR to be at the C-5 methine carbon, with the less mobile isomer on reversed phase LC analysis being the more potent compound, EC 50 = 0.6 nM, and which converted to the more mobile but less potent (EC 50 = 43 nM) isomer upon heating at 55°C. 17 In considering how compounds 46-48 might be generated, it was recognized that hydrogen abstraction at the C-5 methine carbon of 18 would form a classic captodative radical stabilized by the electron donating sulfur atom and the electron withdrawing carbonyl group. 18,19 A radical mechanism is consistent with the formation of 47 by a process involving combination of a C-5 radical with oxygen that would give hydroperoxide A (Scheme 2).…”
Section: 15mentioning
confidence: 99%
See 1 more Smart Citation